2010
DOI: 10.1517/14728210903571667
|View full text |Cite
|
Sign up to set email alerts
|

Anti-endothelin drugs in solid tumors

Abstract: Atrasentan seems to be active in CRPC, although strong scientific evidence is still to be found. Interesting clinical findings regard zibotentan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…In clinical studies (phase I -III) with ABT-627 in prostate cancer, pain was reduced, however, reduction of time to progression and overall survival has not been observed in clinical studies. With Zibotentan, another ET A R antagonist, comparable results were obtained [118]. In a phase II clinical trial using the ET A R antagonist ZD4054 time to progression (primary endpoint) was found not to be statistically different between treatment and placebo groups.…”
Section: The Et-1 Pathwaymentioning
confidence: 72%
See 1 more Smart Citation
“…In clinical studies (phase I -III) with ABT-627 in prostate cancer, pain was reduced, however, reduction of time to progression and overall survival has not been observed in clinical studies. With Zibotentan, another ET A R antagonist, comparable results were obtained [118]. In a phase II clinical trial using the ET A R antagonist ZD4054 time to progression (primary endpoint) was found not to be statistically different between treatment and placebo groups.…”
Section: The Et-1 Pathwaymentioning
confidence: 72%
“…Local ET-1 production by skeletal metastases enhances de novo bone formation via the ET A R leading, eventually, to osteoblastic metastases [28]. Atrasentan (ABT-627) is one of the most potent and selective ET A R antagonist [118]. In a preclinical model of breast cancer, treatment with ABT-627 resulted in significantly less osteoblastic bone metastases and a decrease in Fig.…”
Section: The Et-1 Pathwaymentioning
confidence: 99%
“…Since a role of ET-1 in cancer was first shown in prostate tumors and subsequent work implicated this molecule in prostate cancer bone metastasis, the clinical work was focused on this cancer type (Lalich et al, 2007;Russo et al, 2010). Following a promising Phase II program in advanced metastatic disease, both companies undertook similar Phase III trials which encompassed early metastatic disease, advanced metastatic disease and combination therapy with ET A antagonists and a taxane (the most effective chemotherapeutic in routine practice today).…”
Section: Outcomes Of Previous Clinical Trials In Cancer Patients Usinmentioning
confidence: 99%
“…In the next section, we provide an overview of therapeutic agents shown to slow the progression of prostate cancer-induced metastasis to the skeleton; detailed reviews may be found elsewhere (see Russo et al 2010; Saad and Lipton 2010b; Saylor et al 2013). As the analgesic efficacy for most of these agents in patients with PCIBP has not been reported on, this is a knowledge gap that remains to be addressed.…”
Section: Therapeutic Strategies For the Management Of Pcibpmentioning
confidence: 99%